Low-carbon refurbishments: how passive or active are technologies, users and their interaction? - Topouzi, M (European Council for an Energy-Efficient Economy, 2013)
Current regulatory and other policy trends in housing refurbishments relating to low-carbon performance standards involve complex technologies and systems as well as innovative solutions to achieve the UK’s demanding targets. Performance indicators of domestic refurbishments in general tend to rely heavily upon assumptions of ideal performance of materials, combined systems installed to high standards under specific conditions, and ideal occupant behaviour in operating and interacting with them. Previous studies exploring the influence of socio-technical factors on the UK’s domestic energy use highlight that one of the main reasons for limited success in achieving energy targets is the lack of understanding of how people interact with domestic technology.